Kontribusi Praktik Manajemen Lingkungan terhadap Profitabilitas Perusahaan - Novita, Nova; Yudanto, Salsabila Rizki (Universitas Negeri Padang, 2023)
AbstractPurpose – This study examines the effect of environmental management practices (EMPs) on financial performance. Environmental issues are now a particular concern for companies because investors are increasingly aware of the importance of protecting the environment, and companies are required to be responsible not only in the economic aspect but also in other aspects such as social and environmental.Design/methodology/approach – Financial performance is measured using Return on Assets, while environmental management practice (EMPs) is measured through content analysis, including disclosure of aspects of energy, water, waste, raw materials, emissions, and biodiversity. Through panel data regression using Fixed Effects model.Findings – This research finds that energy efficiency, water efficiency, material management, emissions to water, water, and land, and biodiversity management do not affect financial performance. Only waste management has a positive influence on financial performance.Originality/value – This research tries to identify the Company's environmental management practices through disclosure in annual reports, sustainability reports, or the Company's website. This research contributes to the disclosure checklist indicator, combining disclosure measurements from Ahinful & Tauringana (2019), Global Reporting Initiatives, and SEOJK.04/2020 about sustainability reports.Research limitations/implications – These results indicate that environmental management practices still require regulators' encouragement and market appreciation. Thus, regulation not only stops at the normative level but achieves effective implementation which benefits the Company and supports the achievement of global climate performance targets.Keywords: Environmental management practices, return on asset, legitimacy theory, resource-based views, energy, water, waste, raw materials, emissions, and biodiversity.Article Type: Research Paper